2022
DOI: 10.1038/s41598-022-16764-5
|View full text |Cite
|
Sign up to set email alerts
|

A clinical trial of a patient-customized virtual reality intervention for tinnitus

Abstract: Virtual reality (VR) has recently been used as a clinical treatment because it can efficiently simulate situations that are difficult to control in real-world settings. In our study, we assessed the potential of VR in patients with chronic subjective tinnitus. An evaluation of its clinical benefits was performed based on analyses of patient electroencephalograms (EEGs) and by questionnaire responses after 6–8 weeks of patient involvement in our VR-based alleviation program. Clinical trials were performed at a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Two studies were on internet-based interventions and both demonstrated the therapeutic potential of CBT delivered with added benefits when done under the expert guidance of an audiologist [ 25 , 33 ]. Also, a recent trial reported Virtual Reality as an aiding factor to CBT’s effectiveness with a reported reduction in tinnitus distress [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Two studies were on internet-based interventions and both demonstrated the therapeutic potential of CBT delivered with added benefits when done under the expert guidance of an audiologist [ 25 , 33 ]. Also, a recent trial reported Virtual Reality as an aiding factor to CBT’s effectiveness with a reported reduction in tinnitus distress [ 31 ].…”
Section: Resultsmentioning
confidence: 99%